2019
DOI: 10.1186/s12950-019-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the association of IL-10 polymorphisms in Behcet’s disease: a systematic review and meta-analysis

Abstract: BackgroundPolymorphisms in the interleukin-10 (IL-10) gene have been studied in various ethnic groups for possible association with Behçet’s disease (BD). This study aimed to perform a meta-analysis of eligible studies to calculate the association of IL-10 polymorphisms with BD.A systematic literature search was carried out in PubMed, Embase, Web of Science, and Scopus databases to identify relevant publications, and extracted the respective results. Pooled odds ratio (OR) with 95% confidence interval (CI) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…Ni et al 32 presented an association between IL-10 1082 G allele and risk of developing gastric cancer. Although other meta-analyses have shown the association between IL-10 polymorphisms and other diseases 16 , 31 35 , the present meta-analysis of five case–control studies did not indicate IL-10 SNPs as a risk factor or protective factor for the progression of leishmaniasis.…”
Section: Discussioncontrasting
confidence: 99%
“…Ni et al 32 presented an association between IL-10 1082 G allele and risk of developing gastric cancer. Although other meta-analyses have shown the association between IL-10 polymorphisms and other diseases 16 , 31 35 , the present meta-analysis of five case–control studies did not indicate IL-10 SNPs as a risk factor or protective factor for the progression of leishmaniasis.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown a significant relationship between IL-10 ─ 819 C/T SNP and several diseases, including Alzheimer's disease, lung cancer, and Behcet's disease [13][14][15][16]. We demonstrated that the T allele of the IL-10 ─ 819 gene is associated with higher risks of periodontitis.…”
Section: Discussionmentioning
confidence: 53%
“…At the same time, it suppresses the innate response and thus, might contribute to bacterial persistence and the following chronic infection in the region [12]. Two detected single nucleotide polymorphisms (SNPs) in the promoter region of the IL-10 gene, including at positions − 819 and − 592, are reported to be associated with several diseases [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, two latest meta-analyses were published by Shahriyari et al and Lee and Song. The two publications had collected all current case-control studies and made an updated conclusion on the association between IL-10 polymorphisms and BD risk [39,40].…”
Section: Discussionmentioning
confidence: 99%